Integration of Ornamental Plant Cultivation and Klanceng Bees in Lorejo Tourism Village Development - Chatarina Lilis Suryani; FX Suwarta; Umul Aiman (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Lorejo region is the entrance to the Nanggulan Tourism village, so it is very strategic to develop into an alternative tourist destination. One potential development program is the decorative plant. During the pandemic covid 19, the demand for decoratives plants was high, but after the end of the pandemic declined, and the income of the farmers decreased. Because the types of decorative plants cultivated are seasonal, and their prices fluctuate. Orchids can be chosen for cultivation to make a stable price and the business of integration between the cultivation of honeybees with decorative plants. The purpose of the activity was to increase business continuity and income for decorative plant farmers in groups. Orchid cultivation training can increase the knowledge and skills of cultivating, caring for, and how to breed orchids. Beekeeping training can increase farmers' knowledge about how to propagate colonies, maintenance and care, and plant sources of bee food. Based on monitoring and evaluation, it seems clear that there are prospects for the sustainability of the ornamental plant and bee farming business, even though it has not increased income.